2020
DOI: 10.1002/lary.29041
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of In‐Hospital Costs Following Endoscopic Transphenoidal Pituitary Surgery

Abstract: Objective: To characterize the patient and clinical factors that determine variability in hospital costs following endoscopic transphenoidal pituitary surgery. Methods: All endoscopic transphenoidal pituitary surgeries performed from January 1, 2015, to October 24, 2017, with complete data were evaluated in this retrospective single-institution study. The electronic medical record was reviewed for patient factors, tumor characteristics, and cost variables during each hospital stay. Multivariate linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
2
21
2
Order By: Relevance
“…In contrast to previous studies, we did not find significant associations between costs and age ( 19 ), smoking status ( 14 , 47 ), comorbidities ( 23 , 28 , 47 ), MFI-5 score ( 51 ), Cushing’s disease ( 24 , 44 , 45 ) or readmissions ( 44 , 45 ). Age was not related to higher costs ( 19 ), which may be explained by the higher proportion of complex cases at younger age, compared to more patients with NFAs at higher age.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous studies, we did not find significant associations between costs and age ( 19 ), smoking status ( 14 , 47 ), comorbidities ( 23 , 28 , 47 ), MFI-5 score ( 51 ), Cushing’s disease ( 24 , 44 , 45 ) or readmissions ( 44 , 45 ). Age was not related to higher costs ( 19 ), which may be explained by the higher proportion of complex cases at younger age, compared to more patients with NFAs at higher age.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, we identified factors associated with higher total costs, that are generally well explained by more complex patient and tumour characteristics, or a more complex clinical course ( Figure 3 ). So, increased costs were logically related to healthcare utilization (e.g., longer OR time, LOS, ICU), in concurrence with previous reports ( 5 , 14 16 , 24 , 28 , 44 50 ). Additionally, we found that patients with RCCs, dependent functional status, tumours invading the third ventricle, specific surgical approaches (i.e., combined transsphenoidal/transcranial, intradural, involvement of ENT-surgeon, nasoseptal flap skull base reconstruction) were increased costs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Postoperative CSF leakage is a frequent, serious, and costly complication resulting in a higher risk of meningitis and a longer hospital stay (43,44). The cause of this complication is either lack of recognition of a perioperative CSF leak or an incomplete closure of the leak, but small perioperative CSF leaks are not always noticeable without enhanced visualization (45).…”
Section: Discussionmentioning
confidence: 99%